THE TAPESTRY OF ENGLISH PHRASEOLOGY: WEAVING WORDS INTO FIXED EXPRESSIONS - Shakhnoza Sharofova (Journal of new century innovations, 2024)
Abstract: English phraseology represents a rich and intricate aspect of language, comprising fixed expressions that play a vital role in communication. These expressions, often referred to as idioms, collocations, or formulaic language, are integral to everyday discourse, encapsulating cultural nuances, semantic intricacies, and pragmatic functions. This article provides a comprehensive exploration of English phraseology, examining its origins, classifications, cognitive processing, communicative functions, and pedagogical implications. Drawing upon linguistic theories, empirical studies, and interdisciplinary perspectives, it elucidates the significance of phraseology in language acquisition, language teaching, translation studies, and cross-cultural communication. Through an in-depth analysis, this article unveils the vibrant tapestry of English phraseology, showcasing its dynamic interplay with linguistic creativity, cognitive mechanisms, and societal norms.